PERAN MONITORING DAN EVALUASI TERHADAP SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH - Taufik, Taufeni (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
The results of the evaluation of the implementation of Performance Accountability System ofthe Provincial, Regency / City in Indonesia in 2011, according to the Ministry of PAN &RB (2012), is still not encouraging. Local Government in Indonesia no one gets asatisfactory and well, and still found the Regency / City in Indonesia with a value somewhatless and less. Somewhat less value means local government in Indonesia still have aperformance management system is less reliable, and needs a lot of improvements includingbasic repairs. While the lack of meaning and order of performance management system is notreliable and needs a lot of improvements and changes that are very basic. Lax governmentagency performance accountability system area indicates that the implementation of themonitoring and evaluation has not been run properly. The results of monitoring andevaluation can not be used as material for the repair or improvement programs to localgovernments. Monitoring and evaluation should be useful to give suggestions, feedback orrecommendations for improvement programs - programs that dimonev for the future.Keywords: Monitoring and evaluation, the Government Performance AccountabilitySystem